Economic investigation of a Vanadium Redox BESS for the exploitation of wind power rejections in an isolated Greek Island. (November 2020) - Deiktas, Georgios; Anastasiadis, Anestis G.; Vokas, Georgios A.
Abstract: Greece has plenty of electrically isolated Islands. Most of them, like Crete, Lesvos, or Chios have a great Aeolian Potential which remains un-exploitable due to Power Grid limitations. The aim of this paper is to investigate the possibility of integrating a Vanadium Redox Battery Energy Storage System in order to minimize the unharnessed wind power owing to the local grid limitations. For this purpose, real time series data of theoretical energy production and wind power rejections of two Wind Parks operated in a Medium Size Greek Island which reached the 17% of their theoretical production capability in 2014 will be used. Additionally, the Island load demand hourly variation coming from the archives of the private company that owns the wind parks are used. Based on these data and the electrical model of the Vanadium Redox Batteries (VRB) several simulations for various VRB power/energy capacity combinations were conducted and their capabilities in wind energy recovery were estimated. Afterwards, the simulated systems were examined from the aspect of economic viability with the use of economic indices such as the Internal Rate of Return (IRR) and the Net Present Value (NPV). Finally, the influence on the feasibility of such an investment caused by factors like the selling price of energy provided to the grid based on the VRB initial capital cost found in recent Lazard's Levelized Cost of Storage (LCOS) were examined in detail. Among many significant results drawn by this simulation, it was found that the maximum percentage of the rejected energy that can be exploited (stored) by the batteries is 60% while the 47% can be reinjected back to the Grid, a fact that leads to a relatively expensive selling price of the Energy that comes from the batteries in order to keep the investment feasible.